2008
DOI: 10.1371/journal.pone.0004069
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of CXCR4 Chemokine Receptor Expression in Human Normal and Neoplastic Tissues Using the Novel Rabbit Monoclonal Antibody UMB-2

Abstract: BackgroundThe CXCR4 chemokine receptor regulates migration and homing of cancer cells to specific metastatic sites. Determination of the CXCR4 receptor status will provide predictive information for disease prognosis and possible therapeutic intervention. However, previous attempts to localize CXCR4 using poorly characterized mouse monoclonal or rabbit polyclonal antibodies have produced predominant nuclear and occasional cytoplasmic staining but did not result in the identification of bona fide cell surface r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 28 publications
7
59
0
1
Order By: Relevance
“…Compounds and Antibodies-CXCL12 (PeproTech, Hamburg, Germany), 125 I-CXCL12 (ARI0129, Hartmann Analytic, Braunschweig, Germany), AMD3100 (A5602, Sigma), cycloheximide (C4859, Sigma), -protein phosphatase (P0753, New England Biolabs GmbH, Frankfurt am Main, Germany), CCX733 and 11G8 monoclonal mouse anti-CXCR7 antibody (ChemoCentryx, Mountain View, CA) (22), anti-transferrin receptor antibody (13-6800; Invitrogen), and UMB-2 monoclonal rabbit anti-CXCR4 antibody (23). Polyclonal rabbit antisera against the hemagglutinin (HA) epitope MYPYDVPDYA were generated by injecting the peptide into rabbits 631-633 after coupling to keyhole limpet hemocyanin and emulsification with Freund's adjuvant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds and Antibodies-CXCL12 (PeproTech, Hamburg, Germany), 125 I-CXCL12 (ARI0129, Hartmann Analytic, Braunschweig, Germany), AMD3100 (A5602, Sigma), cycloheximide (C4859, Sigma), -protein phosphatase (P0753, New England Biolabs GmbH, Frankfurt am Main, Germany), CCX733 and 11G8 monoclonal mouse anti-CXCR7 antibody (ChemoCentryx, Mountain View, CA) (22), anti-transferrin receptor antibody (13-6800; Invitrogen), and UMB-2 monoclonal rabbit anti-CXCR4 antibody (23). Polyclonal rabbit antisera against the hemagglutinin (HA) epitope MYPYDVPDYA were generated by injecting the peptide into rabbits 631-633 after coupling to keyhole limpet hemocyanin and emulsification with Freund's adjuvant.…”
Section: Methodsmentioning
confidence: 99%
“…We then addressed CXCL12-dependent phosphorylation of the CXCR7-4tail mutant using the rabbit monoclonal CXCR4 antibody UMB-2, which was raised against a synthetic peptide corresponding to the 22 C-terminal amino acids of CXCR4 (23). Recently, we established that binding of UMB-2 to CXCR4 is severely impaired after CXCL12 stimulation/phosphorylation of CXCR4 and that dephosphorylation of CXCR4 by -PP reinstates binding of UMB-2 to CXCR4 (Fig.…”
Section: Regulation Of Ligand-independent Receptormentioning
confidence: 99%
“…At first, rather basic information is needed, namely a full description of the antibody characteristics (antibody name, manufacturer, code number, antigen sequence if known, species raised in, monoclonal/polyclonal designation, clone designation if applicable, lot number for polyclonal antibodies). It should further be confirmed that the antibody has been tested successfully in cell lines expressing the receptor, and negative controls in cell lines devoid of the receptor or in wild-type/knockout mice should also be provided (3,4,10,11). Preferably, such data should be available for both fresh frozen and the corresponding formalin-fixed materials.…”
Section: Immunohistochemistry Requirementsmentioning
confidence: 96%
“…By definition, GPCRs are cell surface receptors with 7 transmembrane-spanning domains. Therefore, under normal conditions, we expect to see immunoreactivity localized at the cell membrane (10,11,(13)(14)(15). A typical example of the somatostatin receptor sst 2 expressed in a neuroendocrine tumor is shown in Figure 1A.…”
Section: Localization Within Cellsmentioning
confidence: 99%
See 1 more Smart Citation